TACTICS OF THE DENTIST DURING ORTHOPEDIC TREATMENT WITH DIFFERENT PROSTHESIS DESIGNS IN NON-STANDARD CLINICAL SITUATIONS - V.M. Dvornyk; H.M. Kuz; O.I. Teslenko; O.V. Dobrovolska; V.S. Kuz; K.Yu. Nedashkivskyi; K.V. Marchenko (Український стоматологічний альманах)
In the clinic of prosthetic dentistry, when choosing different prosthesis designs, it is mandatory to take into account the condition of the prosthetic bed elements, namely: the presence, number and location of teeth, characteristics of the mucous membrane, and the bone foundation.